3-Dimensional flood inundation model of Pekan sub-district, Pahang using Geographic Information System (GIS) - Ahmad, Zuhairi; Shammodin, Muhammad Shaheed (2016)
Pekan sub-district which covers Pahang River basin is one of the most flood prone area in Pahang. Annual monsoon season during November to March is the main cause of flood which causes economic losses to the locals. The objective of this study is to pro-duce a 3-Dimensional flood inundation model of the area. In the first stage, raw data especially elevation/terrain, bathymetry, and satellite images will be collected from USGS website, Malaysia Remote Sensing Agency (MRSA), and Department of Survey and Mapping Malaysia (JUPEM). Satellite images of Landsat 8 and SPOT 7 were com-bined together to produce an image that covers whole part of Pekan sub-district. Total of 35 ground control points (GCPs) including JUPEM and Royal Malaysian Navy (TLDM) benchmarks was collected for geometric correction in ENVI software using Differential Global Positioning system (DGPS). Collected digital elevation (DEM) and river depth data (bathymetry) was used to project a terrain model in 3-Dimensional view using ArcGIS software. Final product of analyzed images were applied to the ter-rain model to produce a 3D map of Pekan sub-district. The produced 3D map can be used to correlate between river water level and inundated area and thus, flood spreads can be observed and controlled later on. This study is expected to help local authorities in planning ahead to mitigate flood issues in the future.